Effects of antagonists on quisqualate and nicotinic receptor-mediated currents of midbrain neurones in culture - Bijak, Maria; Jarolimek, Wolfgang; Misgeld, Ulrich (British journal of pharmacology, 1991)
1 The action of non-N-methyl-d-aspartate (non-NMDA) and nicotinic antagonists on excitatory postsynaptic currents (e.p.s.cs) and on quisqualate (Quis)- and nicotine-gated currents was studied by use of whole-cell recording in dissociated culture of the rat midbrain. 2 6-Cyano-7-nitroquinoxaline-2,3-dione (CNQX; 0.1 μm) and kynurenic acid (0.1 mm) attenuated network-generated and miniature e.p.s.cs while mecamylamine (100 μm) and hexamethonium (400 μm) had no effect. Acetylcholine (ACh) enhanced or suppressed e.p.s.cs. The suppressing effect of ACh was blocked by atropine (0.1-10 μm). 3 ACh (50-1000 μm) and quisqualate (Quis, 0.1-20 μm) induced inward currents with the same reversal potential as e.p.s.cs. 4 Application of Quis and α-amino-3-hydroxy-5-methylisoxazole-4-propionic acid (AMPA) in a low concentration (0.5 and 5 μm, respectively) evoked a maintained current which was attenuated by CNQX (1 μm) and kynurenic acid (0.5 mm) but not by mecamylamine (100 μm). 5 Higher concentrations of Quis (5-20 μm) and AMPA (50-100 μm) evoked a transient and a maintained current component. Kynurenic acid (1 mm) reduced the transient but not the maintained component. CNQX (5-10 μm) increased the maintained component without reducing the transient one; 20 μm CNQX reduced both components. 6 ACh-induced transient current was mimicked by nicotine and reversibly and dose-dependently blocked by mecamylamine. Atropine (10 μm), hexamethonium (400 μm) as well as CNQX (100 μm) and kynurenic acid (1 mm) did not affect the current. 7 Hexamethonium (50-400 μm) voltage-dependently depressed the maintained current elicited by both Quis and ACh. 8 In conclusion, although the antagonists examined here seem to discriminate between non-NMDA and nicotinic receptor-mediated e.p.s.cs, they vary considerably in respect of their mode of action when tested on Quis, AMPA and ACh-induced currents.
Gesehen am 08.04.2021